(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction: The intriguing link between periodontal disease severity and physical activity remains largely understudied, particularly in the Saudi Arabian population. Thus, the current research was intended to ascertain the effect of physical activity on the prevalence and indicators of periodontal diseases. Materials: The cross-sectional approach with convenience sampling was applied to the recruitment of 160 adult subjects attending gymnasiums, sports clubs, malls, primary health centres, and community dental health programs. Based on IPAQ scores, the participants were split into two distinct groups: a physically active group and a physically inactive group. The two study groups were compared with one another in terms of recorded parameters. The gathered data subsequently underwent statistical processing using SPSS 20.0. Results: Of the 160 subjects, 66.87% (n = 107) had gingivitis and 33.12% (n = 53) periodontitis. A lower mean PI (1.62±0.31) was observed in the physically active group compared to the physically inactive group (6.91±1.12). The physically active group had a mean BI of 19.01±4.53 and the inactive group 69.98±9.29. For physically active and inactive groups, mean PD measurements were 2.49±0.33 mm and 4.61±0.07 mm, respectively.Physically active individuals had a significantly lower mean CAL (2.98±0.88 mm) compared to the inactive group (5.37±1.02 mm). Parametric variances between groups are statistically significant (p<0.001). Conclusion: Insufficient engagement in physical activity has undeniably been identified as a risk factor for the development and severity of periodontal disease, marked by escalated indicators of gingivitis and periodontitis. The study findings unequivocally endorse the adoption of a consistent physical activity regimen as strategic initiatives to proactively address the incidence of inflammatory periodontal diseases. Many patients with different psychophysical characteristics seek periodontal therapy at dental clinics. This study alerts clinicians to the impact of physical inactivity in a wide-spectrum population and helps identify periodontal risk in sedentary patients. It also aids in treatment planning for these periodontally risky, physically inactive people. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S20-S25